Drivers and Mechanisms of the 2021 Pacific Northwest Heatwave. Issue 12 (22nd December 2022) - Schumacher, D. L.; Hauser, M.; Seneviratne, S. I.
Abstract: In late June 2021, western North America, and in particular the Pacific Northwest experienced a heatwave with temperatures usually only encountered in hot desert climates. Using a blend of reanalysis data and Earth System Model (ESM) simulations, we disentangle the physical drivers underlying this exceptional event. Our analysis highlights the role of the anticyclonic circulation aloft, which converted previously gained potential energy—some of which by intense latent heating thousands of kilometers upwind over the North Pacific—back into sensible heat through subsidence. We demonstrate that this upwind latent heat release did not only result in a hot troposphere above the heatwave region, but also contributed directly to escalating near‐surface temperatures. Facilitated by the mountainous terrain and dry soils in the region, deep atmospheric boundary layers were established over the course of several days, connecting the air close to Earth's surface to a massive heat reservoir many kilometers above. Anomalous soil moisture acted to raise the heatwave temperatures by 3°C in a large region during the peak of the event, with local anomalies exceeding 5°C. Overall, we conclude that this heatwave was the outcome of an intricate interplay between dynamic and thermodynamic processes. ESM experiments suggest that the same large‐scale atmospheric circulation fueled by enhanced thermodynamic drivers, such as more available moisture for condensation upwind, could enable even more extreme near‐surface temperatures, in particular in a warmer climate. Plain Language Summary: In late June 2021, western North America, and in particular the Pacific Northwest, experienced temperatures normally encountered in hot deserts. Our analysis highlights the role of the anticyclonic circulation aloft, whose downward spiraling air masses converted previously gained potential energy back into sensible heat. We show that in addition to heating through sinking, the air was previously heated by condensation in ascending air streams thousands of kilometers upwind, over the North Pacific. Together, these processes fostered a massive heat reservoir above the heatwave region, which contributed to escalating near‐surface temperatures through strong vertical mixing. Dry soils in the region intensified surface heating, boosting maximum temperatures in excess of 5°C. Overall, we conclude that this heatwave was the outcome of an intricate interplay of the atmospheric flow and processes such as condensational and surface heating, further exacerbated by human‐induced background warming. Our experiments suggest that if fueled by more available moisture for condensation upwind, the same large‐scale atmospheric circulation could enable even more extreme near‐surface temperatures. Key Points: A strong "Omega Block" enabled the heatwave, yet near‐surface air temperatures were more extreme than suggested by the large‐scale flow Sinking air aloft previously experienced strong latent heating over the North Pacific, contributing to the high near‐surface temperatures Deep atmospheric boundary layers brought the extreme heat down to the surface, with local soil moisture effects in excess of 5°C